PHILOSOPHICAL AND EDUCATIONAL BASIS OF TOLERANCE IN EDUCATION IN THE CONDITIONS OF TRANSFORMATION OF HIGHER EDUCATION (Pedagogy of Higher and Secondary Education, 2022)
In the article, the analysis of such phenomenon in an educational process as tolerance given Torrance is considered from the point of view philosophy of education is signs, value, and prospects of development in a modem educational process. The philosophical educational analysis of tolerance in education is done in the context of transformation  processes which are experienced by domestic higher education.
Keywords: tolerance; education; philosophy of education; educational process; higher education